Intellectual property rights in the Bahamas, Barbados, Guyana, Jamaica, Trinidad & Tobago (Gowling, Strathy & Henderson OttawaCA, 1998)
Assesses the existing status of the intellectual property legislation, administration and enforcement of these countries and makes recommendations for improvement and overal TRIPs compliance.
Keywords: INTELLECTUAL PROPERTY